Square microstrip multi band fractal antenna using EBG structure for wireless applications. Issue 2 (25th January 2020) - Akkole, Suresh; N., Vasudevan
Abstract : Purpose: Application of electromagnetic band gap (EBG) i.e. electromagnetic band gap technique and its use in the design of microstrip antenna and MIC i.e. microwave integrated circuits is becoming more attractive. This paper aims to propose a new type of EBG fractal square patch microstrip multi band fractal antenna structures that are designed and developed. Their performance parameters with and without EBG structures are investigated and minutely compared with respect to the resonance frequency, return loss, a gain of the antenna and voltage standing wave ratio. Design/methodology/approach: The fractal antenna geometries are designed from the fundamental square patch and then EBG structures are introduced. The antenna geometry is optimized using IE3D simulation tool and fabricated on low cost glass epoxy FR4, with 1.6 mm height and dielectric materials constant of 4.4. The prototype is examined by means of the vector network analyzer and antenna patterns are tested on the anechoic chamber. Findings: Combining the square fractal patch antenna with an application of EBG techniques, the gain of microstrip antenna has been risen up and attained good return loss as compared to the antennas without EBG structures. The designs exhibit multi-frequency band characteristics extending in between 1.70 and 7.40 GHz. Also, a decrease in antenna size of 34.84 and 59.02 per cent for the first and second iteration, respectively, is achieved for the antenna second and third without EBG. The experimental results agree with that of simulated values. The presented microstrip antenna finds uses in industrial, scientific and medical (ISM) band, Wi-Fi and C band. This antenna can also be used for satellite and radio detection and range devices for communication purposes. Originality/value: A new type of EBG fractal square patch microstrip antenna structures are designed, developed and compared with and without EBG. Because of the application of EBG techniques, the gain of microstrip antenna has been risen up and attained good return loss as compared to the antennas without EBG structures. The designs exhibit multi-frequency band characteristics extending in between 1.70 and 7.40 GHz, which are useful for Wi-Fi, ISM and C band wireless communication.